Bovine hypodermosis: A review. (2018) - Biswas, Papia; Kumar, Ajit; Lalnunpuia, C.; Lalchhandama, C.; Alam, Seikh Sahanawaz; Bhagawati, Jayashre; Patra, Gautam; Behera, Parthasarathi; Das, Samares Kumar; Ghosh, Subhamoy
No abstract available